Aquatic polymer-based edible films of fish gelatin crosslinked with alginate dialdehyde having enhanced physicochemical properties. (15th February 2021) - Park, Jinseok; Nam, Jeongmin; Yun, Haesung; Jin, Hyoung-Joon; Kwak, Hyo Won
Graphical abstract: Highlights: Fish gelatin films crosslinked with alginate dialdehyde were successfully prepared. The mechanical properties of the crosslinked fish gelatin film were greatly increased. The crosslinking process greatly improved the vulnerability of gelatin in moisture condition. The crosslinked fish gelatin films exhibited enhanced antioxidative capacity. Abstract: Fish-derived gelatin (FG), a raw material for edible films, has recently been spotlighted as an alternative source of mammalian gelatin. However, its low stability under moisture conditions and weak mechanical properties limit its application. In this study, a water-stable and mechanically robust FG film was prepared using alginate dialdehyde (ADA) as an eco-friendly crosslinking agent. The crosslinking process of FG with ADA was easily recognized by the change in the color of the FG/ADA composite film, and the browning index of the FG/ADA film could be correlated well with the actual crosslinking degree. The mechanical strength and Young's modulus of the FG/ADA composite film increased significantly with an increase in the content of the ADA crosslinker. In the case of FG/ADA10, the tensile strength and Young's modulus increased by 400 and 600 %, respectively, compared to those of FG. Remarkably, the FG-ADA crosslinking process greatly decreased the vulnerability of FG in moisture environments. Consequently, the FG/ADA10 film remained stable for 30 days under wet environment. In addition, the FG-ADA crosslinking process could enhance the antioxidative capacity of the FG/ADA edible film. According to this study, FG/ADA composite films fabricated in an effective manner using polymers derived from aquatic species like gelatin from fish and ADA from algae could have practical applications in the edible film-based packaging industry.